Blocking Single-Stranded Transferred DNA Conversion to Double-Stranded Intermediates by Overexpression of Yeast DNA REPLICATION FACTOR A - Dafny-Yelin, Mery (Plant Physiol, 2015)
Agrobacterium tumefaciens delivers its single-stranded transferred DNA (T-strand) into the host cell nucleus, where it can be converted into double-stranded molecules. Various studies have revealed that double-stranded transfer DNA (T-DNA) intermediates can serve as substrates by as yet uncharacterized integration machinery. Nevertheless, the possibility that T-strands are themselves substrates for integration cannot be ruled out. We attempted to block the conversion of T-strands into double-stranded intermediates prior to integration in order to further investigate the route taken by T-DNA molecules on their way to integration. Transgenic tobacco (Nicotiana benthamiana) plants that overexpress three yeast (Saccharomyces cerevisiae) protein subunits of DNA REPLICATION FACTOR A (RFA) were produced. In yeast, these subunits (RFA1–RFA3) function as a complex that can bind single-stranded DNA molecules, promoting the repair of genomic double strand breaks. Overexpression of the RFA complex in tobacco resulted in decreased T-DNA expression, as determined by infection with A. tumefaciens cells carrying the β-glucuronidase intron reporter gene. Gene expression was not blocked when the reporter gene was delivered by microbombardment. Enhanced green fluorescent protein-assisted localization studies indicated that the three-protein complex was predominantly nuclear, thus indicating its function within the plant cell nucleus, possibly by binding naked T-strands and blocking their conversion into double-stranded intermediates. This notion was further supported by the inhibitory effect of RFA expression on the cell-to-cell movement of Bean dwarf mosaic virus, a single-stranded DNA virus. The observation that RFA complex plants dramatically inhibited the transient expression level of T-DNA and only reduced T-DNA integration by 50% suggests that double-stranded T-DNA intermediates, as well as single-stranded T-DNA, play significant roles in the integration process.